PENGARUH STRUKTUR MODAL, RISIKO BISNIS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN ON EQUITY (Studi Empiris pada Perusahaan Property Dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Narko, Tri (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This research aims to test the Return On Equity as well as the influence of capital structure, business risk, company size and sales growth. The samples used in this study are Property and Real Estate companies listed on the Indonesia Stock Exchange in 2015-2019. Sampling in this study using purposive sampling method and obtained by 21 companies. The analysis techniques in this study are Multiple Regression Analysis, hypothesis test using F test simultaneously, and partial t test with 5% level of significance. The results of this study showed that the capital structure, business risk, size of the company and simultaneous sales growth influenced Return On Equtiy at a level of less than 5% which is 0.001. Partially only business risk variables that affect Return On Equity at a level of less than 5% is 0.001. While the capital structure, size of the company and sales growth have no effect on Return On Equity. From the results of processing SPSS produces the equation Y = 0.147 + 0.020X1 + 2.597X2 – 0.004X3 + 0.001X4 + e. While the value of coefficient of determination in this study was 0.447. This means that the ability of independent variables to describe dependent variable variations is 44.7%, while the remaining 55.3% is influenced by other variables not studied in this study